Factors Affecting Employee Performance at Imani Suites Bali - Darma Susila, I Made Gede; Ayu Suriyani, Ni Nyoman; Sudirman, I Made (Jurnal Manajemen Pelayanan Hotel, 2024)
The tourism sector is one of the economic supports of the Indonesian state, where tourism itself is part of the industrial sector with good opportunities and potential to be developed. This study aims to examine the effect of communication and work discipline on employee performance at Imani Suites Bali. This research was conducted with a sample of 48 employees. The sampling technique in this research is using saturated sampling method. Data collection by distributing questionnaires using a Likert scale with a value score of 1-5. The data analysis technique used in this study is multiple linear regression analysis techniques with the Statistical Package Social Science (SPSS) version 25.0 test. The results of this study indicate that Communication partially has a positive and significant effect on Employee Performance. Work Discipline partially has a positive and significant effect on Employee Performance. Communication and Work Discipline simultaneously have a positive and significant effect on Employee Performance. Future research is expected not to fixate on the factors in this study, but can add other factors that might affect employee performance. Keyword: communication, discipline, employee performance, human resources management